Antidepresan Kombinasi Ekstrak Etanol Bunga Cengkeh (Syzygium Aromaticum)Dan Ekstrak Aseton Kulit Pisang (Musa Paradisiaca) Terhadap Peningkatan Aktivitas Lokomotor Dan Penurunan Immobility Time Pada Mencit - Pamilutsih, Putik Mayangsari, Nurcahyanti Wahyuningtyas S.Si., M.Biomed., Apt (2017)
Ethanol extract of clove exhibited antidepressant activity by inhibited monoamine oxidase and reuptake monoamine neurotransmitter receptors as well as aceton extract of banana peels could supply tryptophan into the brain. This study tested the extract combination of clove and banana peels which aimed to increased antidepressant-like activity. In this study uses five treatment groups which each group were given orally with 0.5% CMC-Na, Sertraline 6,5 mg/ kgBB, ethanol extract of clove 200 mg/kgbb, acetone extract of banana peels 200 mg/kgbb, and extract combination of clove and banana peels (1:1) 400 mg/kg during 7 days. Methods for made mice depression used chronic mild stress for 4 weeks and the method used antidepressants test were Tail Suspension Test, Forced Swimming Test and Open Field Test. The result statistically analysis used MANOVA test and continued with LSD (p<0.05). The results showed significant reduced (p<0.05) the immobility time (IT) and climbing , but did not influence of duration of grooming, rearing and central square. The combination extract of clove and banana peels were able to showed antidepressant activity based on a decreased in immobility time (30%) and climbing (50%) compared with control.